PENGARUH TERPAAN IKLAN DAN VIDEO UNBOXING YOUTUBER TERHADAP MINAT BELI KONSUMEN PADA PRODUK POKEMON TCG INDONESIA SERI KOLEKSI VMAX BERKILAU (STUDI PADA POKEMON TCG SEMARANG) - Naufal Farid Jayendar; Joyo Nur Suryanto Gono (Interaksi Online, 2023)
Nowadays, the use of the internet continues to grow rapidly, and so do the social media users in Indonesia. This has made many companies promote their products digitally through various social media. Pokemon TCG Indonesia is one of the companies that promotes through social media. Advertising has been the most popular way of promoting a product. Apart from that, there are also other ways such as using content creators on Youtube to promote products through reviews of these products. This study aims to determine the effect of advertising exposure and YouTuber video unboxing on consumer buying interest in Pokemon TCG Indonesia products, the Sparkling VMAX Collection series. The sampling technique used non-probability sampling with a total sample of 50 people. The testing is done using Simple Regression analysis. The results of the study show that the significance value for the ad exposure variable is 0.000. It means that the ad exposure variable has a positive influence on the purchase intention variable. Furthermore, for the results of the Youtuber video unboxing exposure variable, it shows a significance value of 0.000. It means that Youtuber video.